Strengthening legal protection for teachers and its implications for islamic education in Indonesia: An analytical review of article 39 of law no. 14 - Abdullah; Rochbani, Ita Tryas Nur; Sumianti (Tawazun: Jurnal Pendidikan Islam, 2026)
Law Number 14 of 2005 concerning Teachers and Lecturers affirms the position of teachers as professionals who have a strategic role in the implementation of national education. Article 39 of the law regulates the development and development of the teaching profession as an effort to strengthen the competence, professionalism, and welfare of teachers in a sustainable manner. This research aims to analyze the substance of Article 39 of Law Number 14 of 2005 and examine its implications for Islamic education. The method used is library research in the sense of research that the data collection process uses a data collection approach used through literature study techniques by collecting, analyzing, and synthesizing various relevant literature, including books, scientific journals, articles. The results of the study show that the strengthening of the teacher profession through coaching, competency development, and professional protection has a strong relevance to Islamic educational values, such as trust, professionalism, and moral responsibility in the educational process. The implications of strengthening the teaching profession on Islamic education are reflected in improving the quality of educators, learning effectiveness, and the formation of students' character based on Islamic values. Thus, the implementation of Article 39 of Law Number 14 of 2005 is expected to contribute significantly to improving the quality of Islamic education in Indonesia. Abstrak Undang-Undang Nomor 14 Tahun 2005 tentang Guru dan Dosen menegaskan posisi guru sebagai profesional yang memiliki peran strategis dalam penyelenggaraan pendidikan nasional. Pasal 39 UU mengatur pengembangan dan pengembangan profesi guru sebagai upaya penguatan kompetensi, profesionalisme, dan kesejahteraan guru secara berkelanjutan. Penelitian ini bertujuan untuk menganalisis substansi Pasal 39 UU Nomor 14 Tahun 2005 dan mengkaji implikasinya terhadap pendidikan Islam. Metode yang digunakan adalah penelitian perpustakaan dalam arti penelitian bahwa proses pengumpulan data menggunakan pendekatan pengumpulan data yang digunakan melalui teknik studi literatur dengan mengumpulkan, menganalisis, dan mensintesis berbagai literatur yang relevan, termasuk buku, jurnal ilmiah, artikel. Hasil penelitian menunjukkan bahwa penguatan profesi guru melalui pembinaan, pengembangan kompetensi, dan perlindungan profesi memiliki relevansi yang kuat dengan nilai-nilai pendidikan Islam, seperti kepercayaan, profesionalisme, dan tanggung jawab moral dalam proses pendidikan. Implikasi penguatan profesi guru terhadap pendidikan Islam tercermin dalam peningkatan kualitas pendidik, efektivitas belajar, dan pembentukan karakter siswa berdasarkan nilai-nilai Islam. Dengan demikian, implementasi Pasal 39 UU Nomor 14 Tahun 2005 diharapkan dapat berkontribusi signifikan dalam peningkatan kualitas pendidikan Islam di Indonesia.